Anticarcinogenic activities of sulforaphane are influenced by Nerve Growth Factor in human melanoma A375 cells. (March 2018) - Arcidiacono, Paola; Stabile, Anna Maria; Ragonese, Francesco; Pistilli, Alessandra; Calvieri, Stefano; Bottoni, Ugo; Crisanti, Andrea; Spaccapelo, Roberta; Rende, Mario
Abstract: Melanoma is a severe form of cancer, resistant to conventional therapies. According to in vitro studies, sulforaphane, a dietary component, has been considered a promising antineoplastic candidate. The present study analyzes the in vitro biological effects of sulforaphane in A375 melanoma cell line with or without the addition of Nerve Growth Factor. For the first time, our results show that a supplementation of Nerve Growth Factor partially reverses the sulforaphane-induced: i) inhibition of cell migration, ii) pro apoptotic changes in cell cycle and iii) modulation of active caspase-3. Furthermore, we report the sulforaphane-induced modulation in the expression of Nerve Growth Factor receptors TrKA and p75NTR, shifting their ratio from pro survival to pro apoptotic. In conclusion, the present study evidences that in vivo the antineoplastic effects of sulforaphane may be reduced by the contemporaneous presence of other biological elements such as Nerve Growth Factor and it contributes to a better definition of the real in vivo potentiality of sulforaphane as antineoplastic candidate. Highlights: NGF partially reverses the SFN-induced inhibition of cell migration. NGF partially interferes with SFN-induced changes in cell cycle but not in cell viability. SFN and β-NGF modulate the percentage of p-AKT and active caspase-3. SFN modulates the expression of TrkA and p75NTR and their ratio.